THE EFFECT OF INTERACTIVE BUDGETING ON INDIVIDUAL CREATIVITY THROUGH THE MEDIATION OF ROLE CLARITY - Saputri, Tri Rahayu; Solovida, Grace Tianna (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
This study aims to analyze the effect of interactive budgeting on individual creativity through the clarity of roles as a mediating variable in export furniture companies in Jepara. This study uses interactive budget variables as independent variables, individual creativity as the dependent variable and role clarity as a mediating variable. The method used is quantitative, primary data obtained through distributing questionnaires and analyzed using Partial Least Square (PLS). The sampling technique used purposive sampling method and obtained a sample of 55 export furniture companies in Jepara Regency. The results showed that interactive budgeting had a positive and significant effect on individual creativity, interactive budgeting had a positive and significant effect on role clarity and role clarity had a positive and significant effect on individual creativity. Meanwhile, role clarity mediates the effect of interactive budgeting on individual creativity partially.